Conceptualizing Pornographication: A Lack of Clarity and Problems for Feminist Analysis. (9th May 2016) - Tyler, Meagan; Quek, Kaye
The mainstreaming of pornography, often referred to as pornographication, pornification, or porn-chic, has become a topic of considerable academic and popular interest. In the last 15 years, an expanding academic literature has documented and begun to analyze the increasing consumption and normalization of pornography as well as pornographic imagery. More recently, there has also been a growing concern among policymakers and commentators in the mainstream media about trends labeled "sexualization" and, in particular, the potential consequences of these trends for children. This article begins by sketching out the academic origins of "pornographication" and related terms before considering the different ways that prominent authors have conceptualized them. Recent literature on sexualization is then outlined, with a focus on understanding this in the context of discussions around pornographication. Using a number of examples from key academic texts, and from prominent print media outlets in Australia, we argue that there is a lack of conceptual clarity about pornographication and that pornographication is often conflated with sexualization. We suggest that the lack of clarity in existing literature creates two key issues for feminist analysis: (1) it obscures the role of the pornography industry in the processes of pornographication and (2) it deflects discussion away from the potential harms of the normalization of pornography and pornographic imagery for adult women. It is, therefore, important to clarify and separate the terminology of pornographication and sexualization in order to further critical feminist analyses of these cultural trends.